Generation of Electricity by Vibrating Piezoelectric Crystal in Staircases - Pankaj Aswal; Suyash Kumar Singh; Gayatri Sharma; Pooja Bisht; Shatakshi Singh (Institute of Advanced Engineering and Science, 2017)
A number of renewable or non-renewable sources of energy present these days are not able to meet our need of power. The need of power is increasing day by day as the population is increasing so we are finding different ways to generate power. In this paper we are generating power by walking on the stairs and the power which is generated can be stored for the further use. We can use this system in malls, homes, schools, companies, college, metro etc. When the group of people walk on these stairs, power is generated by the continuous movement of the persons. Here mechanical power is converted into electrical power. The power which is generated can be used to charge mobile.